PENGARUH DOSIS GnRH (Gonadotropin Releasing Hormone) TERHADAP LAMA ESTRUS DAN KUANTITAS KORPUS LUTEUM SAPI PESISIR - Zumarni Zumarni (Jurnal Peternakan, 2013)
This study aims to determine the effect of giving prostaglandin F2α (PGF2α) combined hormone GnRH with different doses of the length of estrous and quantity of the corpus luteum. The material in this study using 12 head Pesisir Cattle age of 3-4 years with a body weight 140,6,87±5.51 kg. The treatment in this study consisted of 3 treatment. A treatment that injection of the hormone GnRH dose of 50 μg PGF2α 48 hours after injection of 5 ml, treatment B injection of the hormone GnRH dose of 100 μg 48 hours after PGF2α injection of 5 ml, treatment C injection of the hormone GnRH dose of 200 μg 48 hours after injection of PGF2α 5 ml. The resulting data were analyzed using Completely Randomized Design with 4 replications. The results showed that the average length of estrous treatment A (18.31±1.22 hours), B (18.50±0.34 hours) and C (17.81±1.28 hours) showed nodiffer significantly (P>0,05) between treatments. The average quantity of the corpus luteum treatment A is with 3.75±1.50; B 5.00±1.55 and C 4.50±0.58 fewer fruits not significantly different (P>0.05) by treatment. From the study it can be concluded that the hormone GnRH 50 μg - 200 μg after injection of PGF2α positive influence on the length of estrous, and the number of corpus luteum.